Store & forward based health monitoring system for old age home - Islam, Tania; Sikander, Mehreen; Emroz, Sehzeen (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.